Involvement of interactive educational platforms in the training of graphic design students using the Figma platform as an example - Borysova, S.; Borysov, V.; Kochergina, S. S.; Spasskova, O.; Kushnarova, N. (NAUN Publication, 2024)
The goal is to provide a rationale for choosing the optimal prototyping and UI/UX design software for teaching design students. The purpose of writing this paper is to determine the optimal tools for teaching UI/UX design students through interactive educational platforms. The research uses the methods of cross-multiple-iteration expert ranking, personal ranking of students, and comparative cross-analysis of the results of expert and user ranking. The ranking results confirmed the choice of tools such as Figma, Adobe XD, InVision, Sketch, and Marvel. The users’ conclusions agree with the experts’ evaluations. Still, the analysis revealed a significant difference in approaches: the gap in user evaluations is 84.6% versus 32.0% for experts, indicating the influence of user empathy and the importance of UI/UX in product perception. Figma was selected as a tool for prototyping and UI/UX design with a median rating of 57.2%, justifying its use in interactive educational programs for future designers, contributing to the development of skilled digital production specialists. Further research is focused on developing detailed educational courses for design students, as well as studying the empathic component of experience for creating ergonomic interfaces.
Keywords: educational course; empathy; prototyping; ranking; User Experience; User Interface